Advanced Technologies of Big Data Processing and Analysis (Academician Publishing Book DOI Portal, 2023)
Introductıon Mihaela Tinca Udristioiu Data And Its Propertıes Adam Dudaš Data Processıng And Analysıs Adam Dudaš Data Samplıng Methods Adam Dudaš Basıcs Of Exploratory Data Analysıs Adam Dudaš Fuzzy Sets. Alžbeta Michalikova Fuzzy Reasonıng Alžbeta Michalikova Usıng Sugeno Method For Data Classıfıcatıon Alžbeta Michalikova Usıng Sugeno Method For Data Approxımatıon Alžbeta Michalikova Introductıon To Optımızatıon Fatih Kılıc Sıngle Layer Neural Network Onder Tutsoy Neural Network Implementatıon Jarmila Škrinarova